Socio-environmental assessment of the impact of the African snail, Lissachatina fulica (Férussac), 1821, on the population of Alto Paraíso de Goiás, Brazil - Cazarin-Oliveira, Lígia Cristina; Fraga, Leonardo Pereira; Lombardi, Manoela Volkweis; Volkweis, Fabiana Sperb [UNESP]; Martins-Silva, Maria Júlia (Universidade Estadual de Maringa, 2022)
The introduction of the African snail Lissachatina fulica worldwide poses a risk to the environment, agriculture and human health. Considered a socio-environmental pest it causes problems to plantations and gardens, in addition to threatening native species. Also, it can be an intermediate host of worms that affect humans and mammals. This work aims to evaluate the socioenvironmental impact caused by L. fulica in Alto Paraíso de Goiás, Goiás, Brazil. Specifically, it aimed to analyze the residents' knowledge about L. fulica, if they were able to recognize the invasive snail and differentiate it from the giant native snail Megalobulimus sp., in addition to the community's ability to carry out actions to combat the invasive species. Semi-structured interviews were conducted, guided by a questionnaire, with the urban population, and an unstructured interview with a health surveillance agent in the municipality. The area of the city was divided into five zones and ten residences were visited in each zone. It was found that the residents most affected by L. fulica are those who live in the most urbanized region of the city, with 86% of respondents reporting seeing the animal in the city center. The presence of the Megalobulimus sp. was reported by four residents in the city's border regions with the native Cerrado. Most of the reports of the African snail in the houses occurred by residents of Alto Paraíso de Goiás who had plants in their backyard and personally took care of them.
Keywords: African snail; invasive species; mollusk; socio-environmental